Climate change and the performance of pressurized irrigation water distribution networks under mediterranean conditions: Impacts and adaptations - Daccache, Andre; Weatherhead, E. K.; Lamaddalena, N. (Ip Publishing, 2010)
Numerous previous studies have modelled the impact of climate change on crop water requirements and hence future water resource needs for irrigated agriculture. Fewer have considered the impacts on the performance of irrigation systems and the required engineering and managerial adaptations. This study considers the impacts and adaptations for a typical pressurized pipe irrigation system. The dry years of the baseline period (1970-90) in the southern part of Italy are expected to become the average or even wet year by the 2050s, according to HadCM3 projections. Under these conditions, the large water distribution systems designed to satisfy the baseline dry years will fail unless appropriate engineering or managerial adaptations are made. The resilience of District 8 of the Sinistra Ofanto to the possible future increase in irrigation demand has been assessed. A stochastic weather generator was used to generate future weather under the IPCC A1 and B1 emissions scenarios, taking into consideration the outputs of the HadCM3 model. A daily water balance model was used to quantify the actual and future peak water demand of the district. The reliability of each hydrant under baseline and future demand was calculated using a stochastic hydraulic model and the failure zones identified. Under the current design, the system can tolerate a peak demand discharge up to 1,500 l.s (-1), which is below the 2050s' average (1,720 l.s(-1)). Above that value, the performance of the system will fall drastically as the number of unreliable hydrants will increase. In the future, assuming the same cropping pattern, the threshold discharge (1,500 l.s(-1)) will be exceeded 80% of the time and, as an average, 20% of the system's hydrants will be failing during the peak demand periods. The adaptation options available to farmers and system managers in response to the increasing demand are discussed.